Incidence and clinical predictors of left ventricular thrombus after ST elevation myocardial infarction as detected by magnetic resonance imaging. (3rd May 2023) - Fardman, A; Massalha, E; Natanzon, S S; Brodov, Y; Goitein, O; Chernomordik, F; Hershkovici, R; Grupper, A; Kuperstein, R; Mazin, I; Matetzky, S; Beigel, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The aim of the current study was to characterize clinical predictors and to develop clinical risk score for left ventricular (LV) thrombus as detected by cardiac magnetic resonance imaging (CMR). Methods: We evaluated 337 patients without known prior coronary disease, who underwent primary percutaneous coronary intervention for STEMI. All patients underwent transthoracic echocardiography (TTE) and CMR during their index hospitalization. We developed a novel prognostic risk model (ThrombScore) to identify patients at risk for LV thrombus development. Results: Upon CMR, LV thrombus was present in 34 patients (10%), of whom 33 (97%) had an anterior wall MI and most (77%) had at least mildly reduced left ventricular ejection fraction (LVEF<45%) upon the first TTE. Sensitivity for thrombus formation of the first and second TTE was 5.9% and 59%, respectively. Multivariate logistic regression model revealed that elevated C reactive protein (CRP) levels, lack of ST-segment elevation (STe) resolution, elevated creatine phosphokinase (CPK) levels, and STe in anterior ECG leads are robust independent predictors of LV thrombus in STEMI patients. These variables were incorporated to construct the ThrombScore: a simple six-point risk model. The odds ratio for thrombus development per one-point increase in the score was 3.2 (95% Confidence Interval 2.1–5.01; p<0.001). Discrimination analysis of the model revealed c-statistics of 0.86 for thrombus development. The model identified three distinct risk categories (I, II and III) with thrombus incidence of 0%, 1.6% and 27.6%, respectively. Conclusions: ThrombScore is a simple, practical, clinical risk model for risk stratification of thrombus formation in patients with STEMI.